Merthyr Tydfil County Borough Souvenir of the General Strike (page 1) (Merthyr Tydfil)
1926-05-12 "Merthyr Tydfil County Borough Souvenir of the General Strike (page 1)" [g0158001.jpg], 3 - 12 May 1926 Local Organisation